Sport as a driver for local development and sustainable tourism - Pioletti, Anna Maria (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales, 2017)
The paper analyses the relationship between sport and tourism. Starting from the literature on sport tourism and tourism sport, we examine the impact of a sporting event in terms of tourist flow in relation to the provision of sporting facilities in the Italian regions. The sport tourism is an original product, taking into account both relations between tourism and sport, but also a real osmosis of sport activities with the touristic ones. Mega events, like the Olympics, or local events, as city marathons, exert an increasingly significant role in positioning the resort in the tourist market, improving image, local amenities and infrastructure in general. Sports tourism could be a driving force for local development, community cohesiveness, economics benefits, social incentives, positioning the localities in the touristic market, improving their image.